PARASITISMO DE HUEVOS Y LARVAS DE HELIOTHIS ZEA (BOODIE) (LEPIDOPTERA: NOCTUIDAE) EN MAIZ EN LA REGION METROPOLITANA, CHILE - Guerrero S., M. A.; Arretz V., P.; Lamborot Ch., L.; Araya, J. E. (Acta Entomológica Chilena, 2022)
Parasitism of Heliothis zea (Boddie) on corn without insecticides was studied in several locations of the Metropolitan Región (Chile), during 1990-92. The egg parasites, Encarsia porteri (Mercet) (Aphelinidae) and Trichogramma minutum Riley (Trichogrammatidae), were obtained. In 1990-91, 0.48% and 4.19% parasitism by E. porteri and T. minutum, respectively, were obtained from 1670 eggs collected. Parasitism began in mid January, with máximum levels (7.94% by E. porteri and 59.15% by T. minutum) late in the season. In 1991-92, E. porteri and T. minutum parasitized 3.07% and 13.40%, respectively, of 4948 eggs collected. Eggs obtained from the foliage and stems got up to 28.57% parasitism by E. porteri, while eggs collected on the styles of the same plants and date had only 0.64% parasitism by this aphelinid. In this season, T. minutum parasitized up to 76.98% and 52.03% of the eggs collected from the styles and foliage, respectively. Of 416 and 1309 larvae collected in 1990-91 and 1991-92, only one and four small specimens, respectively, were parasitized by Campoletis sp. (Ichneumonidae). The low and scarce levels of parasitism of H. zea eggs on the styles and larvae, respectively, allowed over 90% infested ears in this study.